2014
DOI: 10.2310/7750.2013.13051
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Annulare Centrifugum due to Pegylated Interferon-α-2a plus Ribavirin Combination Therapy in a Patient with Chronic Hepatitis C Virus Infection

Abstract: Background: Pegylated interferon-a combined with ribavirin is the current standard treatment for chronic hepatitis C virus infection. During interferon and ribavirin therapy, both local and generalized mucocutaneous adverse reactions have been reported. Erythema annulare centrifugum induced by this therapy regimen has not been reported previously.Case Report: A 29-year-old woman was referred to our clinic for a 1-week history of slightly pruritic annular erythematous eruptions on the lower extremities and hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Erythema annulare centrifugum (EAC) is an uncommon eruption characterized by persistent erythematous annular plaques with central clearing. The precise etiology of EAC is unknown, but some cases appear to be a hypersensitivity reaction to medications , foods , autoimmune disorders , psychological stressors , or malignancy . EAC has also been reported in association with generalized pediculosis ; molluscum contagiosum ; and herpes zoster , Malassezia , dermatophyte , or Candida infections.…”
mentioning
confidence: 99%
“…Erythema annulare centrifugum (EAC) is an uncommon eruption characterized by persistent erythematous annular plaques with central clearing. The precise etiology of EAC is unknown, but some cases appear to be a hypersensitivity reaction to medications , foods , autoimmune disorders , psychological stressors , or malignancy . EAC has also been reported in association with generalized pediculosis ; molluscum contagiosum ; and herpes zoster , Malassezia , dermatophyte , or Candida infections.…”
mentioning
confidence: 99%
“…3 associated pegylated interferon α 2-a (PEG-IFNα-2a)/RBV in 2013, and recently, Gönül et al reported a new case of EAC during PEG-IFNα-2a/RBV combination therapy in a patient with CHC. 4,5 These 2 previous cases received PEG-IFNα-2a, whereas our patient received PEG-IFNα-2b; therefore, it appears that EAC has now been associated with either the α-2a or α-2b types of pegylated interferons. Although we cannot safely exclude that, in our case, the onset of EAC is due to BOC, it is unclear if BOC may have played a role in the development of this dermatosis.…”
mentioning
confidence: 64%
“…4 Remote cutaneous reactions that were reported with IFN therapy include vitiligo, pityriasis rosea, trichomegaly, vasculitis, allergic eczema, and erythema annulare centrifigum. 5 Variable forms of granulomatous reactions were reported in association with IFN therapy. The reaction may be localized to the injection site, 6 disseminated on the skin, 7 or systemic with involvement of internal organs.…”
Section: Introductionmentioning
confidence: 98%